A Cost-Effectiveness Analysis of Fosfomycin: A Single-Dose Antibiotic Therapy for Treatment of Uncomplicated Urinary Tract Infection - Morgan Kassabian; Michael S Calderwood; Robert Ohsfeldt (SAGE Publishing, 2022)
Nitrofurantoin, trimethoprim-sulfamethoxazole (TMP-SMX) and fosfomycin are first-line therapeutics for uncomplicated urinary tract infections (uUTI). While fosfomycin is the most expensive, it is also attractive due to its effectiveness against most uUTI-causing bacteria, limited risk of cross-resistance with other drugs, and single-dose delivery. In light of these competing attributes, a cost-effectiveness analysis can provide useful, standardized information about tradeoffs between fosfomycin and treatment alternatives. This paper assessed cost-effectiveness via incremental cost-effectiveness ratios (ICERs) that represented a drug's incremental cost per additional uUTI case resolved with initial course of antibiotic therapy. The study setting was New Hampshire, USA. Total cost of treatment was lowest with TMP-SMX and highest with fosfomycin. ICERs were $84.53 and $78.59 for nitrofurantoin and $2264.29 and $2260.89 for fosfomycin under a payer and societal perspective, respectively. While no standard benchmark for our measure of cost-effectiveness exists, the high national prevalence of antibiotic stewardship efforts suggests that willingness-to-pay to increase the number of people who are successfully treated with an initial course of therapy is non-zero. Ultimately, fosfomycin may currently be considered a cost-effective option for treating uUTI in the US. As a recently off-patent drug, increased competition in the generic market may improve its cost-effectiveness in the future.